The effect of miR-7975 on the malignant phenotype of oral squamous cell carcinoma - GAO Teng, ZHAO Zhenyuan, ZHAO Mengran, LIU Jie, SONG Xiaomeng (Kouqiang yixue)
Objective To investigate the effect of miR-7975 on the malignant phenotype of oral squamous cell carcinoma (OSCC) and its potential mechanisms. Methods This study compared the expression levels of miR-7975 in different oral cell lines by qRT-PCR. miR-7975 mimic and miR-7975 inhibitor were transfected into OSCC cell lines HSC3 and HN4 respectively. Colony formation assay, CCK8 assay, Transwell assay, and wound healing assay were conducted to evaluate the effects of miR-7975 on the malignant phenotype of OSCC cells. Western blot was employed to analyze changes in the expression of EMT related proteins and proteins associated with the RAS/ERK signaling pathway. Subcutaneous tumor model of nude mice was used to further validate the tumorigenic effect of miR-7975 in vivo. Results The expression of miR-7975 was downregulated in OSCC cells. Overexpression of miR-7975 reduced the proliferation, migration, and invasion abilities of OSCC cells, whereas downregulation of miR-7975 enhanced these abilities. After miR-7975 overexpression, the expression of the EMT-related protein E-cadherin was upregulated, while N-cadherin, Vimentin, β-catenin, Snail, and Slug were downregulated. Additionally, the expression of proteins related to the RAS/ERK signaling pathway increased. Conversely, the expression of EMT and RAS/ERK signaling pathway-related proteins showed opposite changes when miR-7975 was downregulated. Compared to the control group, the volume and weight of tumors formed in nude mice were significantly smaller after miR-7975 overexpression, while they were significantly larger when miR-7975 expression was reduced. Conclusion miR-7975 exerts its tumor-suppressive effects by inhibiting the proliferation, migration, and invasion of OSCC through the regulation of EMT and the RAS/ERK signaling pathway.